Reidentification and antifungal susceptibility profile of Candida guilliermondii and Candida famata clinical isolates from a culture collection in Argentina. (28th June 2018) - Taverna, Constanza Giselle; Córdoba, Susana; Vivot, Matías; Szusz, Wanda; Vivot, Walter; Bosco-Borgeat, María Eugenia; Davel, Graciela
Abstract: The aim of this work was to reidentify strains previously identified as Candida guilliermondii and Candida famata by conventional phenotypic methods conserved in a culture collection from Argentina using ribosomal DNA sequencing, ACT1 gene sequencing, and matrix-assisted laser desorption ionization – time of flight mass spectrometry (MALDI-TOF MS). In addition, we performed antifungal susceptibility tests of eight antifungal drugs commonly used in clinical treatment. We identified 68 isolates belonging to the Candida guilliermondii species complex (59 C. guilliermondii, 8 C. fermentati, and 1 Candida carpophila ), 16 isolates belonging to the Candida famata species complex (8 C. famata, 6 Debaryomyces nepalensis, 1 Debaryomyces fabryi, and 1 Debaryomyces tyrocola ). Although sequencing of ITS region was able to identify C. guilliermondii and D. nepalensis isolates, sequencing of ACT1 gene seems to be the most appropriate technique for differentiation between C. fermentati and C. carpophila and between members of the C. famata species complex others than D. nepalensis . MALDI-TOF MS has a good potential for the identification of these yeasts, particularly in clinical laboratories since is a rapid and easy to perform technique. Here, we report the first isolation of D. tyrocola from a human patient and the first isolation of D. nepalensis from lungs and blood of human patients. Finally, correct identification and determination of antifungal susceptibility of those closely related species could be a useful tool for clinicians to choose the most effective antifungal treatment.